Unsettling difference : music drama, the Bible, and the critique of German Jewish identity - Nester, Adi, 1984- (Ithaca : Cornell University Press and Cornell University Library, 2024)
"Unsettling Difference examines the discourse of German Jewish difference and identity as it is expressed in biblical-themed operas, their German-language literary sources, and the aesthetic and intellectual debates that surrounded their creation in the first half of the twentieth century."--
On Jewish difference, the Bible, and the great artwork -- Rudolf Borchardt's Das Buch Joram and the restoration of a biblical language -- Opening the work: the German oratorio and Paul Ben-Haim's Joram -- Moses and Aron representing the people -- On being superfluous: Joseph Roth's Hiob beyond integration -- Inorganic quotations: revisiting assimilation with Eric Zeisl's Hiob.
"A Signale Book" - from titlepage.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on January 08, 2025).
JSTOR
Keywords: Bible -- Influence; Bible -- Influence; Jews -- Germany -- Identity -- History -- 20th century; Jews -- Germany -- Civilization -- History -- 20th century; Juifs -- Allemagne -- Identité -- Histoire -- 20e siècle.; Juifs -- Allemagne -- Civilisation -- Histoire -- 20e siècle.